Introduction to programming with Java : with a problem solving approach - Dean, John , 1962-; Dean, Ray , 1936- (McGraw Hill, 2014)
Teaches the reader how to write programs using Java. This book emphasizes problem solving. It includes an introduction to the Java Collections Framework and an in-depth treatment of recursion. It also includes a "mini-chapter" that describes how to write multiple-method programs in a non-OOP environment.